The determinants that affect the foreign direct investment in China - Chong, Kwok Xiong; Lee, Kar Hing; Phua, Qi Hwa; Tan, Khang Zhe; Tung, Han Lun (2020)
This paper attempts to assess the determinants that affect the FDI in China. It is known that the FDI is crucial for a country’s economic growth as it may stimulate the host country’s development and productivity. Besides, FDI will also bring in many benefits for the host country such as increasing the employment opportunities, stimulating the advancement of technology, improving the managerial skill and so on. Furthermore, since its open door policy in 1978, FDI has played an important role in the country development. Due to its distinctive trade policy reformation in the past ten years, this would drive the motive of the researchers around the world to study the factors behind the success of China. Besides, as the FDI inflows of China started to fluctuate from year 2007 to 2018, these changes of high volatility have created an opportunity to carry out this research which is to examine the factors that will affect the China’s FDI by using the annual data from year 1979 to 2018. Other than that, the Ordinary Least Squares (OLS) method is applied to investigate the relationship between the explanatory variables (trade openness, infrastructure, economic growth, inflation, exchange rate and market size) and the dependent variable (China FDI inflow). Lastly, the empirical results show that the exchange rate, inflation, infrastructure and the market size are significant in affecting the China FDI. It is found that the exchange rate, inflation and the infrastructure are having a positive relationship with the FDI in China. On the other hand, the market size is having a negative relationship with the FDI in China. However, the remaining independent variables like the economic growth and the trade openness were found to be insignificant in impacting the FDI in China.